Back Cover: Halogen Bonding: A New Platform for Achieving Multi‐Stimuli‐Responsive Persistent Phosphorescence (Angew. Chem. Int. Ed. 13/2022). Issue 13 (3rd March 2022) - Dai, Wenbo; Niu, Xiaowei; Wu, Xinghui; Ren, Yue; Zhang, Yongfeng; Li, Gengchen; Su, Han; Lei, Yunxiang; Xiao, Jiawen; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; et al.
Abstract : Halogen bonding is an effective tool in solid‐state supramolecular chemistry to stabilize crystal structures. In their Research Article (e202200236 ), Zhengxu Cai and co‐workers introduced intermolecular halogen bonding (CN⋅⋅⋅Br) into a host—guest room‐temperature phosphorescence (RTP) system, achieving fluorescence—phosphorescence dual emission. The weak intermolecular interactions of the halogen bond are sensitive to external stimuli (heat, mechanical force and X‐rays), realizing colorimetric multi‐stimuli response behavior.